(untitled) (Research, Society and Development, 2022)
Historically, patient safety has become an issue with a wide field for debate since ancient times. However, the theme bases its relevance through the numerous debates that seek to minimize AE’s and iatrogenics, arising from HAIs in ICUs. The objective of this study is to describe which measures are recommended for nursing professionals applied in the intensive care unit to ensure the integrity and reduction of harm to the patient. This is an integrative and bibliographic review of the literature on the GOOGLE ACADEMIC AND SCIELO platforms of articles published between 2014 and 2021, using the descriptors: Patient safety and Intensive care unit. Eleven articles were analyzed where the main adverse events related to HAIs in ICUs were identified, in addition to the topographic sites with the highest incidence of HAIs. With regard to the conduct of the nursing team, actions aimed at controlling and preventing damage should be promoted, in addition to the entire team having technical knowledge, seeking to meet the patient’s needs. It is understood that the monitoring of IRAS in an ICU is a mechanism that optimizes control and prevention actions, and that the standardization of nursing conduct will always be an ally of these professionals. Seeing that most adverse events are preventable, the team’s empathy towards patients will lead to a decrease in HAIs, in addition to providing a humanized care of great value to the unit.